The Mediating Entrepreneurial Self-efficacy Between Entrepreneurship Education, Need For Achievement, and Creativity on Entrepreneurial Intention - Fauzan Lubada; Djoko Dwi Kusumojanto; Aniek Indrawati (Profesional Muda Cendekia Publishing, 2021)
Everyone has the same opportunity to succeed by setting up a business. Through entrepreneurial intentions, it is hoped that someone can develop their potential to open a business. This study aims to determine whether entrepreneurial intentions can be influenced by entrepreneurship education, the need for achievement, creativity, and entrepreneurial self-efficacy in students of the Faculty of Economics, State University of Malang because entrepreneurial intentions are an important factor that can make someone want to set up a business.. This research is a quantitative approach using path analysis. The results showed that entrepreneurial intentions can be influenced by entrepreneurship education, achievement needs, creativity, and self-efficacy. In addition, entrepreneurial self-efficacy can act as a mediation between entrepreneurship education, achievement needs, creativity to entrepreneurial intentions.